Aptamers for the diagnosis and treatment of human glial tumors - T. N. Zamay; M. A. Dymova; A. A. Narodov; A. A. Koshmanova; D. S. Grek; I. I. Voronkovskii; A. K. Gorbushin; A. S. Kichkailo; E. V. Kuligina; V. A. Richter; R. А. Zukov (Сибирский онкологический журнал)
Purpose of the study: to evaluate the feasibility of using functional analogues of protein antibodies – dNa/ RNa aptamers in diagnostics, treatment and prognosis of human brain glial tumors.Material and Methods. The relevant literature sources were searched in scopus, Web of science, pubmed, elibrary with inclusion of publications from 2000 to 2023. sixty articles are presented in the review.Results. The analysis of the literature devoted to classification, diagnostics and therapy of brain glioblastomas was carried out and the feasibility of using for in vivo diagnostics and therapy of this disease aptamers, which are molecular recognition elements based on DNA/RNA oligonucleotides, capable of binding to the given molecular targets and distinguishing even separate functional groups in them, was studied. A list of aptamers to human glial brain tumors and their molecular targets that can be used for diagnostics and therapy of glioblastoma, including tumor imaging by pet/ct, mRi, plasmon resonance, fluorescence and confocal microscopy, etc., is presented. literature data suggest that DNA/RNA aptamers can be used to search for circulating tumor cells in the blood of glioblastoma patients, to target therapeutic drugs to the tumor and to inhibit tumor growth.Conclusion. Brain glioblastoma is a heterogeneous tumor consisting of cells at different stages of malignancy and, accordingly, with a different set of oncogenes. For this reason, a multitarget strategy that includes combined suppression of angiogenesis, invasion, metastasis, proliferation and survival of tumor cells should be proposed for the therapy of this disease. DNA/RNA aptamers tailored to key proteins involved in oncogenic transformation may be suitable candidates for the implementation of multitarget therapy for brain glioblastoma.